ANALISIS KEBUTUHAN BAHAN AJAR BAHASA INDONESIA BERBANTU MULTIMEDIA QR CODE UNTUK SISWA KELAS IV SEKOLAH DASAR - Haryanto, Henzi; Suyitno, Imam; Anggraini, Ade Eka (Jurnal Visi Ilmu Pendidikan, 2025)
This research was conducted in order to see the shortcomings of the need for diverse teaching materials and has not been used as a whole in elementary schools. This limitation is the impetus for educators to develop interactive and innovative media, one of which is developing QR-Code assisted flipbook media in Indonesian language subjects with "Exchange and Exchange" material in grade IV elementary schools. This research uses a type of development method using the ADDIE model. However, this research only reached the development stage. The subjects of this study consisted of students and teachers as material and media experts. The data collection method uses interviews and questionnaire results using a linkert scale. The validation results show that teaching materials can be used with a percentage of 87% with a very good category. However, this teaching material still has shortcomings in the learning process. This teaching material still does not combine games in its development.